'Strong is the new skinny': navigating fitness hype among teenagers in northern Sweden. Issue 5 (13th June 2019) - Wiklund, Emelie; Jonsson, Emma; Coe, Anna-Britt; Wiklund, Maria
ABSTRACT: An increased interest in health, diet, and physical activity exist among young people, in this study termed 'fitness hype'. Viewing the body and health as commodities can be understood as part of a healthism discourse. In this study, we explored how Swedish high school students perceive and negotiate the trend regarding exercise, diet and body ideals. Semi-structured interviews were conducted with ten high school students, aged 16–18 years, from various educational programs and with varying levels of physical activity. Using qualitative content analysis, we developd one overarching theme navigating life satisfaction in the face of an 'unhealthy fitness hype' . Four additional, interrelated categories showed how the young people negotiated this developing trend through: (1) the quest for social recognition and value, (2) social media sets the standards, (3) the paradox of strong and skinny as the new standard, and (4) the need for new safety nets . Our results highlight the young people's perceptions of an excessive and influential focus on health and exercise in contemporary society. They described a fitness hype as exorbitant and unhealthy ideals of body and exercise, and understood this as problematic. Social media was seen as contributing to this hype as a powerful arena for 'the quest for social recognition and value'. While not all the young people felt negatively affected by the fitness hype, they perceived its influence on their lives. Further, body and fitness ideals were gendered. Teenage girls faced the paradox of shaping themselves as 'strong and skinny'. Social ties were recognized as an important safety net, particularly classmates, sports mates, and coaches. Knowledge of these problems from the perspective of young people is crucially needed among health professionals and educators. Further research should explore additional support strategies, and young people's experiences of fitness hype among additional youth groups.